2017
DOI: 10.1016/j.bbr.2016.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hippocampal subfields in verbal and visual episodic memory

Abstract: Introduction: Selective hippocampal (HC) subfield atrophy has been reported in older adults with mild cognitive impairment and Alzheimer’s disease. The goal of this study was to investigate the associations between the volume of hippocampal subfields and visual and verbal episodic memory in cognitively normal older adults. Methods: This study was conducted on a subset of 133 participants from the Einstein Aging Study (EAS), a community-based study of non-demented older adults systematically recruited from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 34 publications
(51 reference statements)
11
72
2
Order By: Relevance
“…Furthermore, previous studies reported correlation between scores of FCSRT free recall and atrophy in the left hippocampus and parahippocampus in AD and MCI subjects [19,20,22]. This finding is concordant with a recent study reporting that either the Rey Complex Figure delayed recall and the FCSRT delayed Recall, visual and a verbal episodic memory tests, are associated with total hippocampal volume in cognitively normal older adults [47]. Moreover, studies with visual tests show association with right hippocampus MCI subjects [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, previous studies reported correlation between scores of FCSRT free recall and atrophy in the left hippocampus and parahippocampus in AD and MCI subjects [19,20,22]. This finding is concordant with a recent study reporting that either the Rey Complex Figure delayed recall and the FCSRT delayed Recall, visual and a verbal episodic memory tests, are associated with total hippocampal volume in cognitively normal older adults [47]. Moreover, studies with visual tests show association with right hippocampus MCI subjects [20].…”
Section: Discussionsupporting
confidence: 88%
“…Next, correlations between gray matter atrophy and Word and Picture free recall scores of the FCSRT were entered as covariates in the design matrix of the VBM analysis for AD patients combined with controls. It has been previously reported [47] that this procedure improves the statistical power to detect brain-behavior relationships. In a third step, an overlap analysis was conducted to identify common regions of gray matter atrophy correlating with both Word and Picture free recall scores.…”
Section: Statistical Analyses For Neuroimaging Data Vbm Analysismentioning
confidence: 99%
“…In the current study, the association between T2*‐RT and delayed recall performances was most prominent in the bilateral subiculum. This finding is generally in line with the results of previous volumetric investigations; a reduced subicular volume was associated with delayed visual and verbal memory recall. However, the relation between T2*‐RT and delayed subicular recall has not been well explored in humans.…”
Section: Discussionsupporting
confidence: 92%
“…The CA1 is a subfield which has been identified as a region of increased vulnerability in the case of prolonged and short-term ischemia (Petito, Feldmann, Pulsinelli, & Plum, 1987;Schmidt-Kastner & Freund, 1991). Subfield specialization research has proposed that the CA3 and DG are associated with early recall and CA1 with consolidation and retrieval of visual information (Mueller, Chao, Berman, & Weiner, 2011;Zammit et al, 2017). Further hypothesis-driven studies are needed to better understand the subfield specialization as it pertains to working memory.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the left hippocampal subfields CA1 and CA2/3 were associated with working memory in youth with CHD. Subfield specialization research has proposed that the CA3 and DG are associated with early recall and CA1 with consolidation and retrieval of visual information (Mueller, Chao, Berman, & Weiner, 2011;Zammit et al, 2017). Subfield specialization research has proposed that the CA3 and DG are associated with early recall and CA1 with consolidation and retrieval of visual information (Mueller, Chao, Berman, & Weiner, 2011;Zammit et al, 2017).…”
Section: T a B L E 4 Brief-a Mean Score Differences Between Chd And Cmentioning
confidence: 99%